If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 26 = 52 Reorder the terms: 26 + 9x = 52 Solving 26 + 9x = 52 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + 9x = 52 + -26 Combine like terms: 26 + -26 = 0 0 + 9x = 52 + -26 9x = 52 + -26 Combine like terms: 52 + -26 = 26 9x = 26 Divide each side by '9'. x = 2.888888889 Simplifying x = 2.888888889
| 3y+3=3x | | -1/2x-4.5=2x-3 | | 12=e^2x | | y=10+0.5 | | (x^2+8x+16)(x+14)=y+1 | | Y-5y=3 | | v=pi*y^2*h | | 5=-(1-2h)-3(h-3) | | 3ax+2ay+3bx+2by= | | 14x^3-2x^2+8X=0 | | V=pi | | 20l+2w=340 | | 5+19x-4x^2=0 | | (X-13)3=8 | | 8x-8=10x+20 | | -5(-3-2x)=11x | | 3+2n=-4 | | 29x=7(4x-5) | | 4t^2+15t+9=9 | | 9x=8(x+1) | | 4b-(3-2b)-6=90 | | 16x-2x=13 | | 8-0.3w=1.72w+2.75 | | 0.5=-2+3x | | 3(7)-5y=(-11) | | 21x^2-165x-216=0 | | 121=5x+6y | | 3(4x)-1-2x=0 | | 2x-35=180 | | 6x=10-y | | 21m^2-90m-75=0 | | 0.15x+3.75y=28.35 |